Why do people with OCD and health anxiety seek reassurance excessively? An investigation of differences and similarities in Function - Halldorsson, B; Salkovskis, P (Springer Nature, 2017)
Excessive reassurance seeking (ERS) is commonly reported in patients who have OCD or health anxiety. Despite its prevalence and associated risk of ongoing difficulties, little is known about the function of ERS. It has been conceptualised as a type of compulsive checking behaviour, but could also be seen as being a supportive maneuver. This study offers a new approach towards defining ERS and support seeking (SS), and similarities between these two constructs in a sample of OCD and health anxious patients. A semi-structured interview was employed. Participants reflected on the nature and goals of their reassurance and support seeking-its impact on themselves and other people. Twenty interviews were conducted, transcribed and analysed in accordance to framework thematic analysis. Six overarching themes were identified in terms of ERS and five for SS. Results revealed limited diagnosis specificity of ERS. Strikingly, participants with health anxiety did not report seeking support.